Peasant Society and Marxist Intellectuals in China : Fang Zhimin and the Origin of a Revolutionary Movement in the Xinjiang Region - Sheel, Kamal, 1950- (Book collections on Project MUSE., 1989)
Whereas most writing on the Communist Revolution in China has concentrated on the influence of intellectual leaders, this book examines the role of peasants in the upheaval, viewing them not as a malleable mass but as a dynamic social force interacting with the radical intelligentsia. Focusing on the Xinjiang region, Kamal Sheel traces the historical roots of the early twentieth-century agrarian crisis that led to a large-scale revolution in the late 1920s, one of the most successful peasant movements organized by the Chinese Communists. A fresh analysis emerges of the remarkable Marxist in.